Demineralized dentin matrix (DDM) from human teeth increases osteoblasts and type i collagen density after tooth extraction: an experimental study - Dewi, Renie Kumala; Oktawati, Sri; Gani, Asdar; Suhartono, Eko; Hamrun, Nurlinda; Ganesh, Rajendran; Sapphira, Nadira; Aurenada, Syabita (Padjadjaran Journal of Dentistry, 2025)
Introduction: Post-extraction cavities must be promptly treated to minimize alveolar ridge resorption. Various bone graft materials can be used to encourage bone regeneration in perialveolar defects. Demineralized Dentin Matrix (DDM) is a bone graft material found in human tooth dentin containing type I collagen. The content of DDM is expected to show an increase in mediators that form bone, such as osteoblasts, thereby accelerating the bone healing process. The study aims to analyze the effect of DDM on osteoblast count and type I collagen density during post-extraction bone healing. Methods: This true experimental study used guinea pigs with extracted left mandibular incisors. Sockets were filled with (1) polyethylene glycol gel (control group, n=9) or (2) DDM gel (treatment group, n=9). The gel was inserted into the socket until it was full and then sutured with non-absorbable silk. The guinea pigs were euthanized on days 7, 14, and 21 for osteoblast counting and type I collagen density measurement. One-way ANOVA was used to assess osteoblast numbers, while the Kruskal-Wallis test was applied to analyze type I collagen density. Results: The treatment group exhibited a higher osteoblast count on day 7 (48.73), day 14 (79.00), and day 21 (89.66) compared to the control group (day 7: 33.00, day 14: 59.6, day 21: 78.27). A statistically significant difference was observed between the treatment and control groups in osteoblast count (p = 0.000) and type I collagen density (p = 0.009). Conclusion: DDM increases osteoblast numbers and type I collagen density on days 7, 14, and 21 post-extraction, potentially enhancing bone remodeling